Effects of increasing dietary L-glutamine to replace antibiotics on pig health and performance following weaning and transport. Issue 3 (26th August 2020) - Duttlinger, Alan W; Kpodo, Kouassi R; Schinckel, Allan P; Richert, Brian T; Johnson, Jay S
Abstract: Supplementing nursery diets with 0.20% L-glutamine (GLN) may provide similar growth and health benefits as dietary antibiotics, but it was unknown if greater inclusion levels may provide additional benefits. Therefore, the study objective was to evaluate the impact of replacing dietary antibiotics with increasing GLN levels on growth performance, therapeutic antibiotic treatment rates, welfare measures, and production costs in pigs after weaning and transport. We hypothesized that withholding dietary antibiotics may negatively impact performance and increase therapeutic treatment rate, and that diet supplementation with 0.20% to 1.00% GLN may incrementally improve productivity and reduce therapeutic antibiotic treatment rates compared with dietary antibiotics. Mixed sex pigs ( N = 308; 5.64 ± 0.06 kg body weight [BW]) were weaned (19.1 ± 0.2 d of age) and transported in central Indiana in 2017. Pigs were blocked by BW and allotted to one of seven dietary treatments ( n = 8 pens/dietary treatment): dietary antibiotics (positive control [PC]; chlortetracycline [441 mg/kg] + tiamulin [38.6 mg/kg]), no antibiotics or added GLN (negative control [NC]), 0.20% GLN, 0.40% GLN, 0.60% GLN, 0.80% GLN, or 1.00% GLN fed for 14 d. From d 14 to 35, pigs were provided nonantibiotic common diets in two phases. Overall, average daily gain (ADG) was reduced ( P = 0.01; 17.7%) from d 0 to 14 in NC, 0.20% GLN, 0.60% GLN, 0.80% GLN, and 1.00% GLN pigs compared with PC pigs, but no ADG differences were detected between 0.40% GLN pigs and PC pigs. Increasing GLN in the diet tended to increase ADG (linear; P = 0.10). Overall, d 35 BW was greater ( P = 0.01) in 0.80% GLN and PC pigs compared with NC, 0.20% GLN, and 0.60% GLN pigs, and was greater for 0.40% GLN and 1.00% GLN pigs vs. 0.20% GLN pigs. However, no d 35 BW differences were detected ( P > 0.05) between PC, 0.40% GLN, 0.80% GLN, and 1.00% GLN pigs. Increasing GLN in the diet tended to increase (linear; P = 0.08) d 35 BW. Overall, income over feed and therapeutic injectable antibiotics cost (IOFAC) for enteric and unthrifty challenges were greater ( P = 0.02) in 0.80% GLN pigs compared with NC, 0.20% GLN, and 0.60% GLN pigs, but no IOFACs for enteric and unthrifty challenges differences were detected between 0.80% GLN pigs and 0.40% GLN, 1.00% GLN, and PC pigs. In conclusion, GLN supplemented pigs had improved performance after weaning and transport compared with the NC pigs with 0.40% GLN being the most effective level.